2013
DOI: 10.3758/s13428-013-0401-7
|View full text |Cite
|
Sign up to set email alerts
|

Thin slices of creativity: Using single-word utterances to assess creative cognition

Abstract: We investigated the hypothesis that individual differences in creative cognition can be manifest even in brief responses, such as single-word utterances. Participants (n = 193) were instructed to say a verb upon seeing a noun displayed on a computer screen and were cued to respond creatively to half of the nouns. For every noun–verb pair (72 pairs per subject), we assessed the semantic distance between the noun and the verb, using latent semantic analysis (LSA). Semantic distance was higher in the cued ("creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
212
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(229 citation statements)
references
References 58 publications
(71 reference statements)
14
212
2
1
Order By: Relevance
“…Indeed, the high openness group had significantly more unique responses than the moderate and low openness groups, which did not differ. This finding is consistent with previous research, which demonstrated that people high in openness provide a greater number of unique associations (Prabhakaran et al, 2014).…”
Section: Unique Responsessupporting
confidence: 83%
See 2 more Smart Citations
“…Indeed, the high openness group had significantly more unique responses than the moderate and low openness groups, which did not differ. This finding is consistent with previous research, which demonstrated that people high in openness provide a greater number of unique associations (Prabhakaran et al, 2014).…”
Section: Unique Responsessupporting
confidence: 83%
“…LSA has also been used on other semantic creativity tasks to measure the remoteness of associations (Beaty, Christensen, Benedek, Silvia, & Schacter, 2017;Green, 2016;Prabhakaran, Green, & Gray, 2014). For instance, Prabhakaran et al (2014) examined the semantic distance of verbs from nouns that were produced during a verb generation task.…”
Section: Divergent Thinking Divergent Thinking (Dt) Is a Common Proxmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, career experience among elementary students helped enhance their creativity (Jyung et al, 2012). Short cues stimulated student creativity in making activities (Prabhakaran, Green, & Gray, 2014). Long-term writings were shown to enhance student creativity (Cho, 2006) as did science programs with space recognition (Kim, Kwon, & Lee, 2011).…”
Section: Cognitive Factorsmentioning
confidence: 99%
“…With the exception of Prabhakaran, Green and Gray (2014), who showed that participants given the cue "be creative" produced responses with a higher mean semantic distance, few studies have attempted to systematically manipulate the associative hierarchies, or semantic networks, of participants.…”
Section: Introductionmentioning
confidence: 99%